Designing a Global Learning Environment. (September 2018) - Stone, Nancy J.; Mara Bazley, Conne; Robertson, Michelle M.; Larson, Nancy LJ; Blickensderfer, Elizabeth L.; Boring, Ronald Laurids
The increase in Massive Open Online Courses (MOOCs) and other "in-the-moment" learning opportunities suggests the need for an understanding of how to effectively design the global learning environment, which includes more than the content, but also includes the modes of delivery or instructional design, as well as the environment in which the learner receives the content. Therefore, not only must the learning environment match the learning content, but also the technologies used and the characteristics of the learners (e.g., engagement, self-regulated learning). Additionally, the likelihood that online learners are multitasking while interacting with the learning material makes it important to understand other aspects of the learners' selected environment. Unfortunately, there is little research on the learners' environment in which the student interacts with the online materials. The purpose of this panel is to address and highlight these issues and offer suggestions for designing effective global learning environments.